(untitled) (Journal of Asian Development Studies, 2025)
This study investigates the critical issues and challenges surrounding effective urban governance in Pakistan, focusing on sustainable urban development as a central concern. Employing a systematic review of scholarly literature published after 2010, the analysis highlights the pivotal role of cities in driving Pakistan’s economic growth and development. However, the rapid pace of urbanisation, coupled with inadequate attention to sustainability, poses serious challenges for urban planning and management. Findings underscore the urgent need to integrate sustainable development principles into all dimensions of urban growth, particularly the socioeconomic and environmental domains. Addressing these challenges is essential to enhance urban productivity, mitigate the adverse effects of pollution and climate change, and ensure the long-term resilience of urban ecosystems. The study calls for evidence based policy measures and strategic planning to promote sustainable urbanisation, enabling balanced economic growth and environmental conservation for future generations.